Increasing food system resilience for nutrition sensitivity and sustainability: A decentralized analysis for India - Kumar, K. Nirmal Ravi; Babu, Suresh Chandra (International Food Policy Research Institute, 2018)
Enhancing food security in vulnerable regions requires both short- and long-term investments. Even though targeted interventions are needed for short-term relief, building resilient food systems is crucial for providing continued food and nutrition security. Resilient food systems have the capacity to bounce back to normal or higher levels of food supply after a shock. Moreover, tracking and measuring food system resilience is critical. Because the current system lacks indicators to measure food system resilience, this paper develops a conceptual framework that can be used to measure food system resilience. We use nutrition sensitivity and sustainability of the food system as the key indicators of food system resilience outcomes. Because changes in food consumption patterns can impact both the nutrition sensitivity of a food system and its sustainability, we analyze the food consumption patterns at the national, state, and district levels in the context of India, and use the results of this analysis to provide strategies to build a resilient food system. Changes in food consumption patterns offer opportunities for introducing new foods into the farming system and can have significant implications for achieving food system resilience.